ANALISIS TINGKAT KEPUASAN PETANI PADI SAWAH TERHADAP KINERJA PENYULUH PERTANIAN LAPANGAN DI KECAMATAN PANDAWAI KABUPATEN SUMBA TIMUR - Insan Pebruwandi Saragih; Elfis Umbu Katongu Retang (Universitas Galuh, 2022)
Extension in agriculture is a policy tool used by the government in an effort to encourage agricultural development. However, on the other hand, farmers have the freedom, namely to accept or reject the program offered in extension activities, so it can be concluded that extension will achieve its goals if the desired changes are in accordance with what farmers expect. The suitability of the level of farmers' expectations with the level of performance of the extension workers is an important factor that greatly affects the level of satisfaction of farmers with the extension activities they get. This study aims to analyze the suitability between the level of expectations of farmers to the level of performance of the agricultural instructor based on the service attributes of the agricultural extension, and the level of satisfaction of farmers in general with the performance of the agricultural instructor. This research was conducted in Pandawai District, East Sumba Regency, from July 2021 to September 2021, where this research is a qualitative descriptive study, using the Importance Performance Analysis (IPA) and Costomer Satisfaction Index (CSI) analysis methods. The results of calculations using the IPA method show that the level of conformity of farmers' expectations on the performance of the extension workers based on the service attributes of the extension workers reaches 77.02%, where the attribute with the highest level of conformity is the attribute of the instructor preparing reading materials, food and drinks during the extension. The attribute with the lowest level of suitability is the attribute of the extension agent assisting farmers/farmer groups in planning farming activities. The results of the CSI analysis of the level of satisfaction of lowland rice farmers on the performance of agricultural extension workers in Pandawai District is 0.66. This value is in the range of 0.66-0.80. These results identify that the level of satisfaction of lowland rice farmers with the performance of extension workers in Pandawai District is in the satisfied category.